2005
DOI: 10.2516/ogst:2005056
|View full text |Cite
|
Sign up to set email alerts
|

In Situ EXAFS Study of the Sulfidation of an Hydrotreating Catalyst Doped with a Non Chelating Organic Additive

Abstract: Résumé -Étude par absorption X in situ de la sulfuration d'un catalyseur d'hydrotraitement dopé par un composé organique non chélatant -Un catalyseur industriel de type CoMoP supporté sur alumine a été imprégné à sec par une solution aqueuse de diéthyleneglycolbutyléther (DEGbe) puis séché à 393 K pendant 12 h. Après activation sous H 2 /H 2 S, ce catalyseur se révèle plus actif que la référence non modifiée. Afin de comprendre l'effet de cet additif organique sur la cinétique de sulfuration, des analyses in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…However, other investigators have reported significant improvements in the HDS activity of commercial (calcined) CoMo/alumina formulations through modification with glycols. For instance, Mazoyer found enhanced activity in both tetralin hydrogenation and 4,6‐dimethyl‐DBT HDS (about 33 and 48 %, respectively) of CoMo/Al 2 O 3 catalysts impregnated with diethyleneglycol n ‐butylether. Additionally, increased selectivity to products from the direct desulphuration route (Scheme ) suggested better promotion of MoS 2 crystals by Co .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other investigators have reported significant improvements in the HDS activity of commercial (calcined) CoMo/alumina formulations through modification with glycols. For instance, Mazoyer found enhanced activity in both tetralin hydrogenation and 4,6‐dimethyl‐DBT HDS (about 33 and 48 %, respectively) of CoMo/Al 2 O 3 catalysts impregnated with diethyleneglycol n ‐butylether. Additionally, increased selectivity to products from the direct desulphuration route (Scheme ) suggested better promotion of MoS 2 crystals by Co .…”
Section: Resultsmentioning
confidence: 99%
“…[46] However, other investigators have reported significant improvements in the HDS activity of commercial (calcined) CoMo/ alumina formulations through modification with glycols. For instance, Mazoyer [47] found enhanced activity in both tetralin hydrogenation and 4,6-dimethyl-DBT HDS (about 33 and 48 %, respectively) of CoMo/Al 2 O 3 catalysts impregnated with diethyleneglycol n-butylether. Additionally, increased selectivity to products from the direct desulphuration route (Scheme 2) suggested better promotion of MoS 2 crystals by Co. [48,49] Further, according to Geantet et al, [9] an industrial calcined CoMoP catalyst impregnated with TEG in an aqueous solution increased its HDS activity by more than twice when tested in desulphurization of both 4,6-dimethyl-DBT and real feedstock (straight-run gas oil).…”
Section: -mentioning
confidence: 99%
“…Two main distinct families of additives can be distinguished: glycol-type agents and chelating or complexing agents. The use of glycol-type agents was largely employed to optimize the preparation of MoS 2 -based catalysts [12,[17][18][19]. The main effect of glycol-type agents seems to be related to a redispersion of molybdic species at the catalyst surface leading to a higher proportion of less polymerized heteropolymolybdate species containing also cobalt, particularly for phosphorus-doped CoMo catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding non-chelating ligands as HDS catalysts additive so far no general agreement about the origin of their beneficial influence has been reached. It appears that enhanced HDS activity could be originated by a number of factors [3][4][5][6][7][8][9]. For instance, for P-doped CoMo/ Al 2 O 3 formulations impregnated in glycols presence it has been proposed that the interaction of the organic additive with both basic OH groups and coordinatively unsaturated Al 3+ sites on the alumina surface could partially prevent Co diphosphopentamolybdate (Strandberg heteropolyanions [10]) complexes decomposition during their deposition on the carrier [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, close proximity of Co and Mo in those complexes could result in formation of increased amount of the socalled "CoMoS phase" during sulfiding. Others [7] found optimized promoter integration to MoS 2 phase in catalysts prepared in presence of glycols (di-ethyleneglycolbutylether). They observed that Mo and Co sulfidation took place at temperatures up to 473 K, this fact probably contributing to better integration of cobalt promoter to edge sites of molybdenum sulfide particles.…”
Section: Introductionmentioning
confidence: 99%